The language realization of the role of women as anthropocentric subjects in Sundanese culture - Awaliah, Yatun Romdonah; Kosasih, Dede; Widyastuti, Temmy; Sutisna, Ade; Hendrayana, Dian (Indonesian Journal of Applied Linguistics, 2024)
Local culture often inherits a patriarchal view that regards women as the second gender category. However, this stereotyped view is only partially correct, especially when looking at the extent to which Sundanese culture views, defines, and places the role of women. Women in the local Sundanese culture have a role as balance keepers in the sense of anthropocentrism. This study aims to describe the role of women as anthropocentric subjects in Sundanese culture. The data of this study were taken from the film Ambu (2019), which represents women's roles in the Sundanese culture, especially as shown in the Baduy tribe. This study is descriptive-qualitative. It used Fairclough's Critical Discourse Analysis approach. This framework enables the film to be studied through its discursive dialogues and scenes, examining how these elements reflect and engage with social and cultural practices. The findings show that the film portrays a representation of women through Ambu Misnah, who embodies gender balance in Sundanese culture, challenging traditional views of domestication. As a cultural symbol connected to Sunan Ambu, her role contrasts with liberal feminist ideals, highlighting a more localized form of female empowerment. Furthermore, the language used by a male character, specifically the head of the Baduy Tribe, reflects a transfer of authority, signaling a shift in gender-power relations. Thus, these findings emphasize an anthropocentric awareness of the role of women, particularly within the Sundanese community.